Analisis Spasial Daya Dukung Lahan Kabupaten Majalengka - Mardalena, Ayu; Banurea, Dedy Swandy; Purwanti, Renita (DEMOS: Journal of Demography, Ethnography and Social Transformation, 2024)
Majalengka Regency is one of the administrative areas in West Java Province which has a high population density of 1,096 people/km2. The large population density in this area results in a large amount of land conversion which can cause a decrease in the carrying capacity of land in Majalengka Regency. This study aims to analyze the land carrying capacity of each sub-district in the Majalengka Regency and analyze the efforts that can be made based on the physical characteristics of the region and the RTRW of the Majalengka Regency. The methods used are descriptive quantitative and spatial analysis in the evaluation of land suitability. The results of this study are that out of 26 sub-districts in Majalengka Regency, 18 sub-districts are included in the deficit category while 8 sub-districts are included in the surplus category. Efforts in the management of each region are different according to the characteristics of the local area and the direction of regional functions based on the RTRW.